SOSIALISASI AUDIT DAN PENGENDALIAN RISIKO DALAM ORGANISASI DI SEKOLAH SMA NEGERI 4 KOTA SERANG (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service activity aims to increase the understanding of SMA Negeri 4 Serang City students about the importance of audit and risk control in school organizations. The main problem raised is the low awareness and knowledge of students in terms of managing and supervising organizational activities. The implementation of activities is carried out through the licensing process, direct observation, counseling, and evaluation using Google Form. The material is divided into three parts, namely an explanation of audits and their objectives, the different types of audits in the organization, and the definition and stages of risk control, which is then followed by a discussion of case studies. The results of the activity showed an increase in student awareness of the importance of recording, reporting, and internal supervision of the organization. It is hoped that this activity can form a more accountable mindset and encourage improvements in student organizational governance.